2015
DOI: 10.19071/jpc.2015.v43.i3.2854
|View full text |Cite
|
Sign up to set email alerts
|

Physiological comparison of root trainer and polybag plants of Hevea brasiliensis

Abstract: <div><table cellspacing="0" cellpadding="0" align="center"><tbody><tr><td align="left" valign="top"><p>The physiology of   root trainer plants in comparison to polybag plants of two popular <em>Hevea </em>clones,   RRII 105 and RRII 430 was studied. Dry matter partitioning and physiological   parameters like leaf water potential, relative water content, chlorophyll   content, PS II activity and photosynthetic efficiency were studied in root   trainer and polybag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Arg.) by Sumesh et al (2015), Salisu et al (2018) and Shobha et al (2019), coffee (Coffea arabica L.) by Srigandha (2017) and Arjun tree (Terminalia arjuna Roxb.) by Nayagam and Varghese (2015).…”
Section: Rld Vsdmentioning
confidence: 98%
“…Arg.) by Sumesh et al (2015), Salisu et al (2018) and Shobha et al (2019), coffee (Coffea arabica L.) by Srigandha (2017) and Arjun tree (Terminalia arjuna Roxb.) by Nayagam and Varghese (2015).…”
Section: Rld Vsdmentioning
confidence: 98%
“…Even still, the authors noted that the higher root-shoot ratio of D40 seedlings compared with polybag seedlings was potentially more favorable for dry outplanting conditions. In another study, researchers found higher physiological function of Hevea seedlings grown in polybags compared with Rootrainers™ and attributed this to "root confinement" [50]. This finding indicates that seedlings were grown too long in the Rootrainers™ and the results were due to a mismatch between the growing schedule and the container size.…”
Section: Comparison Challengesmentioning
confidence: 99%
“…According to some studies, drought reduced the growth and yield of the rubber tree [3,25,26]. Only one drought-tolerant rubber clone, RRIM 600, has been identified and is being used in dry areas of Thailand and India [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%